The Unyielding Enigma - Hima John; Jiss Mary; Jeslin James; S Devu (Journal of Indian Academy of Oral Medicine and Radiology)
Scleroderma, an autoimmune connective tissue disorder marked by profound fibrosis in visceral organs, skin, and blood vessels, exhibits oral manifestations typically initiating with tongue rigidity and facial skin alterations. It presents with a plethora of radiological and systemic presentations. This case report details the clinical and radiographic features of a 45-year-old female and a 30-year-old male, both presenting classic manifestations of the disease and a short review of literature has been made.